Critical Limb Ischemia: Laporan kasus - Quedarusman, Hermanto; Lasut, Pearla (Universitas Sam Ratulangi, 2019)
Abstract: We reported a case of 56 years old man with critical limb ischemia. Diagnosis was made based on anamnesis, signs and clinical symptoms, as well as investigations that included the presence of rest pain in the left leg. Patient also had a history of diabetes mellitus. Echo- doppler and angiographic investigations supported the diagnosis of critical limb ischemia. In this patient, medicamentous treatment has been administered consisted of antiplatelet and cilostazol, blood sugar control by using insulin. The patient also underwent endovascular revascularization.Keywords: critical limb ischemia, peripheral artery diseaseAbstrak: Telah dilaporkan kasus critical limb ischemia pada seorang laki-laki berusia 56 tahun dengan keluhan nyeri seperti terbakar pada kaki kiri bahkan saat istirahat dengan riwayat diabetes melitus. Hasil pemeriksaan penunjang echo-doppler dan angiografi menyokong terdapatnya critical limb ischemia. Diagnosis ditegakkan berdasarkan anamnesis, tanda dan gejala klinis, serta pemeriksaan penunjang. Pada pasien ini, diberikan penatalaksanaan terapi medikamentosa yaitu antiplatelet dan cilostazol, kontrol gula darah dengan menggunakan insulin, dan dilakukan tindakan revaskularisasi endovaskular.Kata kunci: critical limb ischemia, peripheral artery disease